Mathematics and statistics for financial risk management - Miller, Michael B. (Michael Bernard) 1973- (Wiley finance, 2013)
This is an excellent book to grasp the basics of financial risk management. Everything in the book is explained from scratch and the concepts are very well exemplified with real life situations. Accompanied with a website filled with excel sheets for application, the book is great for future course material. This Second Edition of Mathematics and Statistics for Financial Risk Management includes 2 new chapters. The first chapter is on Bayesian Analysis and covers Bayes' Theorem, Many State Problems, Continuous Distributions, Bayesian Networks, and Bayesian Networks versus Correlation Matrices. The second new chapter is on Hypothesis Testing & Confidence Intervals and is on The Sample Mean Revisited, Sample Variance Revisited, Confidence Intervals, Hypothesis Testing, Chebyshev's Inequality, and Application: VaR. All chapters will have problems for testing and answers online.